TERMINATING WORKERS DURING THE PANDEMIC: A PERSPECTIVE ON LEGAL CERTAINTY - Yetniwati Yetniwati; Muskibah Muskibah; Iskandar Zulkarnain (Universitas Syiah Kuala, 2023)
This paper presents a comprehensive analysis of the legal principles that govern the process of worker layoffs and the corresponding legal framework required to regulate such actions during economic crises. The study adopts a normative juridical approach, and the findings highlight the key legal principles that underpin employee terminations and form the basis of legal dogmatics. These principles include clarity, fairness, balance, empowerment, nationality, utility, non-discrimination law, and family principles. Furthermore, the regulatory framework governing employment termination should encompass a minimum set of legally mandated components. These components include clearly defined grounds for termination, prerequisites for initiating the process, procedural steps to be followed, a prescribed time limit for completion, normative entitlements of affected workers, and the implementation of online-based oversight mechanisms. Establishing regulations on employee termination in response to the global economic crisis is of utmost importance. These regulations should incorporate a baseline of legal principles and minimum legal requirements. It is recommended that governmental and legislative entities include provisions for employee terminations within the framework of the Labour Law.